2012
DOI: 10.1073/pnas.1203126109
|View full text |Cite
|
Sign up to set email alerts
|

Functional epialleles at an endogenous human centromere

Abstract: Human centromeres are defined by megabases of homogenous alpha-satellite DNA arrays that are packaged into specialized chromatin marked by the centromeric histone variant, centromeric protein A (CENP-A). Although most human chromosomes have a single higher-order repeat (HOR) array of alpha satellites, several chromosomes have more than one HOR array. Homo sapiens chromosome 17 (HSA17) has two juxtaposed HOR arrays, D17Z1 and D17Z1-B. Only D17Z1 has been linked to CENP-A chromatin assembly. Here, we use human a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
99
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 37 publications
4
99
2
Order By: Relevance
“…Human artificial chromosomes were identified for five of the six higherorder repeat constructs tested (Table 1). In the cases of DXZ1 and D17Z1B, our data are consistent with previous reports (7,(43)(44)(45). The one higher-order repeat construct that did not support formation of human artificial chromosomes was a construct containing D19Z1 alpha satellite, which, perhaps notably, contains the lowest CENP-B box density with the most varied motif periodicity among the alpha satellite arrays tested here.…”
Section: Assessment Of Alpha Satellite Sequence Variation In An Indivsupporting
confidence: 82%
“…Human artificial chromosomes were identified for five of the six higherorder repeat constructs tested (Table 1). In the cases of DXZ1 and D17Z1B, our data are consistent with previous reports (7,(43)(44)(45). The one higher-order repeat construct that did not support formation of human artificial chromosomes was a construct containing D19Z1 alpha satellite, which, perhaps notably, contains the lowest CENP-B box density with the most varied motif periodicity among the alpha satellite arrays tested here.…”
Section: Assessment Of Alpha Satellite Sequence Variation In An Indivsupporting
confidence: 82%
“…We used CENPA immunostaining and CENPA ChIP-PCR to assign the location of centromere assembly, so that each HSA17 in our data set was functionally characterized before proceeding to the analysis of molecular variation (Table 1; Supplemental Fig. S1; Maloney et al 2012). Our data from previously published studies suggested that variation within the HORs of D17Z1 arrays could be linked to centromere location on HSA17 (Maloney et al 2012).…”
Section: D17z1 Hor Sequence Variation Is Associated With Metastable Cmentioning
confidence: 84%
“…There is little contiguous sequence information between D17Z1-B/D17Z1 and D17Z1/ D17Z1-C; however, BAC end sequencing supports that the arrays are essentially adjacent (Rudd et al 2006). In previous studies, we demonstrated that the functional centromere on HSA17 is assembled at either D17Z1 or D17Z1-B (Maloney et al 2012). We showed that in ∼70% of individuals studied, the centromere is assembled at D17Z1, while in 30% of individuals, the centromere is assembled at D17Z1 on one homolog and at D17Z1-B on the other HSA17 homolog.…”
mentioning
confidence: 99%
See 2 more Smart Citations